DEVELOPING SNAKES AND LADDERS MEDIA TO TEACH SPEAKING SKILL - rohman, lutfi (Teaching English as Foreign Language, Literature and Linguisticss, 2022)
This study aims to develop snakes and ladders media, which is integrated in English to determine the level of attractiveness and feasibility of using it, and to find out the response of students after using the snake and ladder media integrated with English. The research method adapts to the development model developed by (Borg and Gall, 1989). The study used the following seven steps: (1) potential problems, (2) data collection, (3) product design, (4) product validation, (5) product revision, (6) product trial, (7) product revision. The data collection tools used are: material expert questionnaires and media expert questionnaires as well as educator response questionnaires to determine product feasibility, student response questionnaires are used to determine product attractiveness. The results of the research that have been developed obtained a design in the form of a snake and ladder media integrated with English in classroom learning, obtaining a feasibility percentage of 4.2 by material experts, 3.9 by media experts, and 4.4 by educators. The percentage of participants' responses to the attractiveness of the product obtained 6.6. Based on the results of the description above, the product developed by the researcher is feasible to be used as a learning medium.